Effects of a high intensity laser in the binding energy of a donor impurity D0 - Castellanos Jerez, Armando; Vega Vargas, Leonardo (TECCIENCIA, 2014)
In this paper, we present theoretical results on the effects of an intense laser on the binding energy in the ground state of a neutral donor impurity D° located in a gaas-(Ga,Al)As quantum well, embedded in a quantum wire. We calculated the behavior of the binding energy, considering different parameters such as the radius of the wire, the intensity of the laser beam, different concentrations of aluminum in the heterostructure, and the position of the impurity within the quantum well. By varying the latter parameter, we observed a new behavior of this energy in the presence of an intense laser.